Preparation method of solid-state electrolyte membrane and solid-state battery

By ball milling and regulating the roughness and particle size of solid electrolyte particles, combined with the preliminary filling and pressing treatment, the problems of decreasing ion conductivity and large volume change rate in the traditional solid electrolyte membrane preparation method are solved, and higher ion transport capability and battery cycling performance are achieved.

CN119650827APending Publication Date: 2025-03-18QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843016.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional solid electrolyte membrane preparation methods lead to a decrease in ion conductivity and a large volume change rate, affecting battery performance.

Method used

By ball milling the solid electrolyte particles, their roughness and particle size are regulated, more particles enter the porous matrix, and preliminary filling and pressing are performed to prepare a dense solid electrolyte membrane.

Benefits of technology

The ion transport capability and density of the solid electrolyte membrane are improved, the volume change rate is reduced, the good contact between the solid electrolyte membrane and the electrode in the battery is ensured, and the circulation performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188371340000171
    Figure BDA0005188371340000171
  • Figure BDA0005188371340000181
    Figure BDA0005188371340000181
  • Figure BDA0005188371340000191
    Figure BDA0005188371340000191
Patent Text Reader

Abstract

The invention relates to a preparation method of a solid electrolyte membrane and a solid-state battery. The preparation method comprises the following steps: S1, carrying out ball milling treatment on solid electrolyte particles to prepare a first material, and after ball milling, enabling the roughness Ra of the solid electrolyte particles to be more than 1 and less than or equal to 1.2 and the granularity D50 to be 1-10 microns; s2, laying a second material at least comprising the first material on the surface of one side of the porous substrate, and carrying out preliminary filling treatment to prepare a solid electrolyte membrane intermediate; and S3, carrying out pressing treatment on the solid electrolyte membrane intermediate to prepare the solid electrolyte membrane. According to the invention, by regulating and controlling the roughness and granularity of the solid electrolyte particles, more solid electrolyte particles enter the porous matrix and are more compactly stacked in the pores, and the volume change rate during switching in different pressure environments is relatively small, so that the solid electrolyte membrane and the electrode always keep good contact in the battery, and the service life of the battery is prolonged. And the good cycle performance of the battery is ensured. And on the other hand, more solid electrolyte particles enter the porous matrix and are more compactly stacked in pores, so that the ion transmission capability and density of the solid electrolyte membrane are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a solid electrolyte membrane and a solid-state battery. Background Art

[0002] In order to ensure the flexibility and stability of the solid electrolyte membrane, the traditional process usually adopts the method of pressing the solid electrolyte particles into the porous matrix to prepare the solid electrolyte membrane. However, the solid electrolyte membrane prepared by the traditional process has the following problems: compared with the solid electrolyte membrane formed by directly pressing the solid electrolyte particles, the ion conductivity decreases. At the same time, the volume change rate of the solid electrolyte membrane is large. This is because the solid electrolyte membrane is pressed with a large pressure during preparation, but the pressure is small in actual use, and the porous matrix will rebound. The degree of rebound of the porous matrix is ​​greater than that of the solid electrolyte particles, which may cause a void area between the contact between the solid electrolyte and the electrode, affecting the transmission of lithium ions inside the battery, resulting in battery performance degradation. Summary of the invention

[0003] Based on this, in order to address the above problems, the present application provides a method for preparing a solid electrolyte membrane and a solid-state battery to solve the above technical problems.

[0004] The first aspect of the present application provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0005] S1, ball-milling the solid electrolyte particles to obtain a first material;

[0006] After ball milling, the roughness Ra of the solid electrolyte particles satisfies 1<Ra≤1.2, and the particle size D50 of the solid electrolyte particles is 1μm~10μm;

[0007] S2, laying a second material including at least the first material on one side surface of the porous substrate, performing a preliminary filling treatment, and obtaining a solid electrolyte membrane intermediate;

[0008] S3. Pressing the solid electrolyte membrane intermediate to obtain a solid electrolyte membrane.

[0009] In one embodiment, in step S1, the temperature of the ball milling process is -50°C to 25°C.

[0010] In one embodiment, in step S1, the rotation speed of the ball milling process is 400 r / min to 700 r / min.

[0011] In one embodiment, in step S1 , the ball milling treatment time is 5 h to 15 h.

[0012] In one embodiment, in step S1, the ball-to-material ratio of the ball milling process is 15:1 to 25:1.

[0013] In one embodiment, in step S1, double grinding balls or triple grinding balls with different particle sizes are used in combination to perform the ball milling process.

[0014] In one embodiment, in step S1 , the flow energy of the first material is 200 mJ to 600 mJ.

[0015] In one embodiment, in step S2, the preliminary filling treatment step includes using a vibrating screen to vibrate the porous matrix after the second material is laid.

[0016] In a preferred embodiment, the number of oscillations is 1 to 5 times.

[0017] In one embodiment, in step S2, the preliminary filling treatment step includes using a flexible roller to roll the second material on the porous substrate to achieve preliminary filling and redistribution of the second material.

[0018] In a preferred embodiment, the number of rolling is 1 to 5 times.

[0019] In one embodiment, before step S2, the method further includes mixing the first material with the fiberizable binder and performing a fiberization treatment to obtain the second material.

[0020] In one embodiment, in step S3, the pressure of the pressing process is 2t-3t.

[0021] In one embodiment, in step S3, the pressing time is 30 seconds to 5 minutes.

[0022] In one embodiment, in step S3, the temperature of the pressing process is 80°C to 130°C.

[0023] In one embodiment, in step S3, the pressing process is performed once.

[0024] The second aspect of the present application provides a solid electrolyte membrane prepared by the preparation method described in the first aspect.

[0025] A third aspect of the present application provides a solid-state battery, comprising a solid electrolyte membrane prepared by the preparation method described in the first aspect.

[0026] In this application, by adjusting the roughness and particle size of the solid electrolyte particles, more solid electrolyte particles are allowed to enter the porous matrix, the accumulation in the pores is more compact, and the volume change rate when switching between different pressure environments is small, so that the solid electrolyte membrane and the electrode always maintain good contact in the battery, ensuring good battery cycle performance. On the other hand, since more solid electrolyte particles enter the porous matrix and the accumulation in the pores is more compact, the ion transmission capacity and density of the solid electrolyte membrane are improved. DETAILED DESCRIPTION

[0027] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0028] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100-150nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0037] In the traditional process, the solid electrolyte membrane is usually prepared by pressing the solid electrolyte particles into the porous matrix. It is understandable that due to the porous structure of the porous matrix, its elasticity is good. The solid electrolyte particles in the ordinary solid electrolyte membrane are relatively loosely stacked in the porous matrix. Under high pressure, the entire solid electrolyte membrane is compressed to a large extent. However, in the battery, under low pressure, the porous matrix tends to return to its original state. The solid electrolyte particles in the porous matrix are not elastic. Only a small number of solid electrolyte particles will rebound with the porous matrix, resulting in less solid electrolyte on the surface of the solid electrolyte membrane in contact with the electrode, and the contact is degraded, affecting the battery performance.

[0038] In order to solve the above problems, the first aspect of the present application provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0039] S1. Ball milling the solid electrolyte particles to obtain a first material.

[0040] S2. Laying a second material including at least the first material on one side surface of the porous substrate, performing a preliminary filling treatment, and obtaining a solid electrolyte membrane intermediate.

[0041] S3. Pressing the solid electrolyte membrane intermediate to obtain a solid electrolyte membrane.

[0042] Wherein, after ball milling, the roughness Ra of the solid electrolyte particles satisfies 1<Ra≤1.2, including but not limited to 1.01, 1.05, 1.1, 1.15, 1.2.

[0043] In the present application, the roughness Ra is defined as follows: assuming that the outer perimeter of the projection of the solid electrolyte particle is L1, the perimeter of the circumscribed circle or ellipse of the projection of the solid electrolyte particle with the largest area is L2, and the roughness Ra = L1 / L2.

[0044] Specifically, a certain number of solid electrolyte particles can be weighed and calculated through scanning electron microscope images.

[0045] The particle size D50 of the solid electrolyte particles is 1 μm to 10 μm, including but not limited to 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0046] In this application, by adjusting the roughness and particle size of the solid electrolyte particles, more solid electrolyte particles are allowed to enter the porous matrix, the accumulation in the pores is more compact, and the volume change rate when switching between different pressure environments is small, so that the solid electrolyte membrane and the electrode always maintain good contact in the battery, ensuring good battery cycle performance. On the other hand, since more solid electrolyte particles enter the porous matrix and the accumulation in the pores is more compact, the ion transmission capacity and density of the solid electrolyte membrane are improved.

[0047] In one embodiment, in step S1, the temperature of the ball milling treatment is -50°C to 25°C, including but not limited to -50°C, -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, and 25°C.

[0048] In one embodiment, in step S1, the rotation speed of the ball milling treatment is 400 r / min to 700 r / min, including but not limited to 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min, and 700 r / min.

[0049] In one embodiment, in step S1, the ball milling treatment time is 5 h to 15 h, including but not limited to 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, and 12 h.

[0050] In one embodiment, in step S1, the ball-to-material ratio of the ball milling process is 15:1 to 25:1, including but not limited to 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, and 25:1.

[0051] In one embodiment, the ball milling process is performed by using two or three grinding balls with different particle sizes.

[0052] In one embodiment, in step S1, small balls with a diameter of 3 mm and large balls with a diameter of 5 mm are used together for the ball milling process, and the ratio of the small balls to the large balls is 3:7.

[0053] In one embodiment, in step S1, grinding balls with a diameter of 1 mm, grinding balls with a diameter of 3 mm, and grinding balls with a diameter of 5 mm are used together for ball milling, and the ratio of the three is 1:3:6 respectively.

[0054] In one embodiment, in step S1 , the flow energy of the first material is 200 mJ to 600 mJ, including but not limited to 200 mJ, 350 mJ, 400 mJ, 500 mJ, and 600 mJ.

[0055] In the present application, the roughness and particle size of the solid electrolyte particles are adjusted to reduce the roughness and particle size of the solid electrolyte particles. The smoother the surface of the solid electrolyte particles, the smaller the particle size, and the smaller the flow energy (the energy required for the powder to flow), which is conducive to more solid electrolyte particles entering the porous matrix, thereby improving the density and ionic conductivity of the solid electrolyte membrane. At the same time, since more solid electrolyte particles are filled into the porous matrix, the accumulation in the pore structure is more compact, and when switching between high-pressure and low-pressure environments, the volume change rate of the solid electrolyte membrane is small, so that in the battery, the solid electrolyte membrane and the electrode always maintain good contact, ensuring good battery cycle performance.

[0056] In one embodiment, in step S2, the preliminary filling treatment step includes using a vibrating screen to vibrate the porous matrix after the second raw material is laid.

[0057] In one embodiment, the method of preliminary filling is to place the solid electrolyte membrane intermediate in a vibrating chamber of a vibrating machine, and vibrate to transfer the second material into the pores of the porous matrix to obtain the solid electrolyte membrane intermediate.

[0058] In one embodiment, the number of oscillations is 1 to 5 times.

[0059] In one embodiment, in step S2, the preliminary filling treatment step includes using a flexible roller to roll the second material on the porous substrate to achieve preliminary filling and redistribution of the second material.

[0060] In a preferred embodiment, the number of rolling is 1 to 5 times.

[0061] In a preferred embodiment, the flexible roller is a sponge roller.

[0062] It is understood that the initial filling mentioned in the present application includes the redistribution process of the raw material (second material) on the surface of the porous matrix. The initial filling is conducive to the uniform distribution of the raw material on the surface of the porous matrix, improves the uniformity of material dispersion in the solid electrolyte membrane, and is conducive to improving the quality of the second material filled in the porous matrix layer per unit area.

[0063] In one embodiment, before step S2, the method further includes mixing the first material with a fiberizable binder and performing a fiberization treatment to obtain the second material.

[0064] In one embodiment, in step S3, the pressure of the pressing treatment is 2t to 3t, including but not limited to 2t, 2.1t, 2.2t, 2.3t, 2.4t, 2.5t, 2.6t, 2.7t, 2.8t, 2.9t, and 3t.

[0065] In one embodiment, in step S3, the pressing treatment time is 0.5 min to 5 min, including but not limited to 0.5 min, 1 min, 2 min, 3 min, 4 min, and 5 min.

[0066] In one embodiment, in step S3, the temperature of the pressing treatment is 80°C to 130°C, including but not limited to 80°C, 90°C, 100°C, 110°C, 120°C, and 130°C.

[0067] In one embodiment, in step S3, the pressing process is performed once.

[0068] In the present application, by regulating the roughness and particle size of the solid electrolyte particles and reducing the flow energy of the raw materials, the production efficiency can be effectively improved and the number of pressing processes can be reduced. A dense solid electrolyte membrane can be formed after only one pressing process.

[0069] In one embodiment, the types of solid electrolyte particles include one or more of oxide solid electrolyte, sulfide solid electrolyte, halide solid electrolyte, hydride solid electrolyte, boride solid electrolyte, and nitride solid electrolyte.

[0070] Specifically, the oxide solid electrolyte is composed of oxide solid electrolyte particles, and may include one or more garnet ceramics, LISICON type oxides, NASICON type oxides, and perovskite type ceramics. For example, one or more garnet ceramics may be selected from the group consisting of: Li 6.5 LqCy 1.75Te 0.25 O 12 、Li7La3Zr2O 12 、Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 and combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li14Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. One or more NASICON-type oxides may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example: in certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. One or more perovskite-type ceramics may be selected from the group consisting of: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1. 3Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25), and combinations thereof. In one variant, one or more oxide-based materials may have an ionic conductivity greater than or equal to about 10 -5 S / cm to less than or equal to about 10 -1 S / cm.

[0071] The sulfide solid electrolyte consists of sulfide solid electrolyte particles and may include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 , Li7P3S 11 , Li9P3S9O3, Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li(Ge 0.5 Sn 0.5 )P2S 12 , Li 10 GeP2S12 (LGPS), Li6PS5X (where X is Cl, Br, or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 、Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 、Li 10 SiP2S 12 、Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、(1 - x)P2S 5-x Li2S (where 0.5 ≤ x ≤ 0.7) and combinations thereof. In one variant, one or more sulfide-based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 1 S / cm.

[0072] Halide solid electrolytes may consist of halide solid electrolyte particles, including Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li2ZrCl6, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1) and combinations thereof. In one variant, one or more halide-based materials may have an ionic conductivity greater than or equal to about 10 -8 S / cm to less than or equal to about 10 -1 S / cm.

[0073] Hydride solid electrolytes consist of hydride solid electrolyte particles, and the hydride-based particles may include one or more hydride-based materials selected from the group consisting of: Li3AlH6, LiBH4, LiBH4 - Li X (where X is one of Cl, Br, and I), LiNH2, Li2NH, LiBH4 - LiNH2, and combinations thereof. In one variant, one or more hydride-based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.

[0074] The boride solid electrolyte is composed of borate solid electrolyte particles, including one or more borate-based materials from the group consisting of Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof. In one variation, the one or more borate-based materials may have a carbon content greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm ionic conductivity.

[0075] The nitride solid electrolyte is composed of nitride solid electrolyte particles, including Li3N, Li7PN4, LiSi2N3, LiPON, and combinations thereof. In one variation, one or more nitride-based materials may have a carbon content greater than or equal to about 10 -9 S / cm to an ionic conductivity of less than or equal to about 1 S / cm.

[0076] Furthermore, the solid electrolyte particles are halide solid electrolyte particles. On the one hand, the halide solid electrolyte particles have high ion conductivity; on the other hand, compared with other inorganic solid electrolyte particles, the halide solid electrolyte particles have a lower Young's modulus, which is conducive to the regulation of their roughness.

[0077] In one embodiment, the particle size D50 of the first material is 2 μm to 5 μm, including but not limited to 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm.

[0078] In the present application, the particle size of the solid electrolyte particles is adjusted to reduce the flow energy of the solid electrolyte particles and improve the filling rate of the solid electrolyte particles in the porous matrix. However, if the particle size is too large, the ionic conductivity of the solid electrolyte membrane will decrease, and if the particle size is small, it is easy to react with water and oxygen. Therefore, the particle size D50 of the first material is preferably 2μm to 5μm.

[0079] In one embodiment, the porosity of the porous matrix is ​​60% to 95%, including but not limited to 60%, 65%, 70%, 75%, 80%, 85%, 90%, and 95%.

[0080] In one embodiment, the thickness of the porous matrix is ​​10 μm to 100 μm, including but not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm.

[0081] In one embodiment, the porous matrix includes, but is not limited to, one or more of non-woven fabrics, aramid films, polyolefin films, cellulose films, glass fiber fabrics, and melt-blown fabrics.

[0082] In the traditional preparation process, in the step of filling the raw materials into the porous matrix, the utilization rate of the raw materials is about 10%. However, by adopting the technical solution of the present application, after one pressing treatment, the utilization rate of the raw materials (i.e., the second material) is ≥30%, which is higher than the 10% of the traditional preparation process.

[0083] It can be understood that the raw material utilization rate here refers to: the mass of the laying raw material and the mass of the raw material entering the porous matrix.

[0084] In one embodiment, the second material further includes a fibrillated binder, which further increases the bonding ability between the solid electrolyte particles and the porous matrix, and prevents the solid electrolyte particles from escaping from the side of the porous matrix away from the raw material laying direction during the pressing process.

[0085] If there is too much binder, it will first take up a certain amount of space, which is not conducive to filling more solid electrolyte particles in the porous matrix and is not conducive to improving the lithium ion transmission capacity of the solid electrolyte membrane.

[0086] Therefore, in one embodiment, based on the mass of the second material as 100%, the mass percentage of the fiberizable binder is 0.1% to 1%, including but not limited to 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, and 1%.

[0087] In one embodiment, the fiberizable binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.

[0088] In one embodiment, before step S2, the method further includes mixing the first material with a fiberizable binder and performing a fiberization treatment to obtain a second material.

[0089] The second aspect of the present application provides a solid electrolyte membrane prepared by the preparation method provided in the first aspect.

[0090] In one embodiment, the porosity of the prepared solid electrolyte membrane is 0.1%-7%, including but not limited to 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, and 7%.

[0091] In one embodiment, under no pressure, the thickness ratio of the solid electrolyte membrane to the porous matrix (without filling) is (0.95-1.1): 1. That is, in the solid electrolyte membrane prepared by the preparation method of the present application, more solid electrolyte particles enter the pore structure of the porous matrix rather than being deposited on the surface of the porous matrix.

[0092] The third aspect of the present application provides a solid-state battery, comprising a solid electrolyte membrane prepared by the preparation method provided by the first aspect above.

[0093] Solid-state batteries also include a positive electrode and a negative electrode.

[0094] In one embodiment, the positive electrode includes a positive electrode plate, a positive electrode tab is extended from the positive electrode plate, and the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer formed on the current collector.

[0095] The positive electrode active material layer includes a positive electrode active material, which is a compound capable of reversibly intercalating and deintercalating lithium.

[0096] In one embodiment, the positive electrode active material comprises one or more transition metal cations, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V) and combinations thereof.

[0097] In one embodiment, the positive electrode active material is one of a layered oxide, a spinel, and a polyanion. For example, the layered oxide (e.g., a rock salt layered oxide) comprises one or more lithium-based positive electrode active materials selected from the group consisting of LiCoO2 (LCO), LiNi x Mn y Co 1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi 1-x-y Co x Al y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O2 (where 0≤x≤1), and LiMO2 (where M is one of Mn, Ni, Co and Al and 0≤x≤1). The spinel contains one or more lithium-based positive active materials selected from the group consisting of LiMn2O4 (LMO) and LiNixMn 1.5 O4. The olivine type contains one or more lithium-based positive electrode active materials LiMPO4 (wherein M is at least one of Fe, Ni, Co and Mn). The polyanion cation contains, for example, phosphates such as LiV2(PO4)3 and / or silicates such as LiFeSiO4.

[0098] In one embodiment, the mass percentage of the positive electrode active material contained in the positive electrode active material layer can be 50wt% to 97wt%, such as 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 97wt%, etc., preferably 80wt% to 90wt%.

[0099] In one embodiment, the positive electrode further includes a positive electrode binder, which is used to bind components such as the positive electrode active material, the positive electrode conductive material, and the positive electrode current collector together. Specifically, the positive electrode binder includes a fiberized binder. Preferably, the fiberized binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polypropylene, polyethylene, and polyimide.

[0100] In one embodiment, the mass percentage of the positive electrode binder contained in the positive electrode active material layer may be 1 wt% to 20 wt%, such as 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, etc., preferably 1.2 wt% to 10 wt%.

[0101] In one embodiment, the positive electrode further includes a positive electrode conductive material, which is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular limitation on it in the embodiments of the present application, as long as it has conductivity without causing chemical changes. Specifically, the positive electrode conductive material may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the positive electrode conductive material may preferably be carbon black.

[0102] In one embodiment, the specific surface area of ​​the positive electrode conductive material can be 80 m 2 / g~200m 2 / g, preferably 100m 2 / g~150m 2 / g.

[0103] In one embodiment, the mass percentage of the positive electrode conductive material contained in the positive electrode active material layer may be 1 wt% to 20 wt%, such as 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, etc., preferably 1.2 wt% to 10 wt%.

[0104] In one embodiment, the thickness of the positive electrode active material layer may be 30 μm to 400 μm, for example 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm to 110 μm.

[0105] In one embodiment, the positive electrode plate also includes a halide solid electrolyte, and the mass proportion of the halide solid electrolyte can be 1wt% to 50wt%, for example, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 30wt%, 40wt%, 50wt%, etc., preferably 10wt% to 20wt%.

[0106] In one embodiment, the positive electrode sheet can be prepared by a dry method, that is, the positive electrode active material, the positive electrode conductive material, the halide solid electrolyte, and the positive electrode binder are mixed. The positive electrode active material, the positive electrode conductive material, and the halide solid electrolyte are mixed first, and then the positive electrode binder is added. Under the action of high shear force, the binder is converted from a powder state to a fibrous state to bond the positive electrode active material, the positive electrode conductive material, and the halide solid electrolyte together, and the positive electrode active electrode material layer is formed by rolling.

[0107] In one embodiment, the negative electrode includes a negative electrode plate, wherein a negative electrode tab is extended from the negative electrode plate.

[0108] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector, wherein the negative electrode active material layer includes at least a negative electrode active material and a negative electrode binder.

[0109] In one embodiment, a carbon material can be selected as the negative electrode active material, and specifically one or more of the following can be selected: graphite, needle coke, amorphous carbon, a carbon-containing mesophase, carbon fiber, and a carbon material with a low degree of graphitization. Among them, graphite can include natural graphite, artificial graphite, etc. In addition, materials obtained by coating them with carbon materials, such as amorphous carbon and graphitized materials, can also be used. Amorphous carbon includes but is not limited to particles obtained by firing the entire mesophase, and particles obtained by infusible treatment and firing of a carbon precursor. As carbonaceous particles with a low degree of graphitization, particles obtained by firing organic matter at a temperature generally below 2500°C can be listed.

[0110] In addition, non-metallic materials that can be used as negative electrode active materials also include silicon and its compounds, such as Si, SiOx (0≤x<2). Since silicon-containing materials are prone to expansion, easy to fall off from the negative electrode current collector, and have poor conductivity, they are often mixed with carbon materials, such as core-shell structures containing carbon coating layers.

[0111] In one embodiment, the mass percentage of the negative electrode active material contained in the negative electrode active material layer can be 80wt% to 99wt%, for example, 80wt%, 85wt%, 90wt%, 95wt%, 97wt%, 99wt%, etc., preferably 95wt% to 97wt%.

[0112] In one embodiment, when the negative electrode active material is a non-metallic material such as a carbon material, the negative electrode binder may be an aqueous binder such as one or more of sodium hydroxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymer, cyclodextrin, etc.;

[0113] In one embodiment, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry. The negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying. The thickener can generally be used to adjust the viscosity of the slurry.

[0114] In one embodiment, the thickener may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.

[0115] In one embodiment, the mass proportion of the thickener in the negative electrode slurry can be 0.1wt% to 5wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc., preferably 0.5wt% to 3wt%, and more preferably 0.6wt% to 2wt%.

[0116] It is understood that the above examples of positive and negative electrodes are only illustrative. Without violating the inventive concept of the present application, any known positive electrode active material, positive electrode binder, positive electrode conductive material, negative electrode active material, negative electrode binder, and negative electrode conductive material can be used in the present application. And the addition of known additives based on actual use requirements should also be considered within the scope of protection of the present application. The present application will be further described below in conjunction with specific embodiments and comparative examples.

[0117] Example 1

[0118] The solid electrolyte particles (Li2ZrCl6) were ball-milled to obtain a first material, the roughness Ra of the first material was 1.05, and the particle size D50 was 5 μm. The ball-milling temperature was -10°C, the rotation speed was 600 r / min, the time was 13 h, and the ball-to-material ratio was 25:1. The flow energy of the first material was 256 mJ.

[0119] The second material is laid on one side surface of the porous substrate and a preliminary filling treatment is performed to obtain a solid electrolyte membrane intermediate. The second material includes the first material and a fiberizable binder PTFE, and the mass ratio of the first material to PTFE is 99:1. The porous substrate is a non-woven fabric with a porosity of 85% and a thickness of 20 μm.

[0120] Specifically, the second material is laid twice on the same side surface of the porous substrate. After each laying, the porous substrate is rolled with a sponge roller to achieve preliminary filling to obtain a solid electrolyte membrane intermediate. 2 10 mg of the second material is laid on the surface of the porous substrate.

[0121] The solid electrolyte membrane intermediate is subjected to a pressing process once to obtain a solid electrolyte membrane, wherein the pressing process is performed at a pressure of 2.5 tons, a time of 1.5 minutes, and a temperature of 120°C.

[0122] Example 2

[0123] The difference between this embodiment and embodiment 1 is that the roughness Ra of the first material is different.

[0124] Example 3

[0125] The difference between this embodiment and embodiment 1 is that the roughness Ra of the first material is different.

[0126] Example 4

[0127] The difference between this embodiment and embodiment 2 is that the particle size of the first material is different.

[0128] Example 5

[0129] The difference between this embodiment and embodiment 2 is that the particle size of the first material is different.

[0130] Example 6

[0131] The difference between this embodiment and embodiment 2 is that the type of solid electrolyte is different.

[0132] Example 7

[0133] This embodiment differs from Embodiment 2 in that the second material does not include a fiberizable binder.

[0134] Example 8

[0135] The difference between this embodiment and embodiment 2 is that the particle size of the first material is different.

[0136] Comparative Example 1

[0137] The difference between this comparative example and Example 2 is that the roughness Ra of the first material is not adjusted.

[0138] The test parameters of the embodiments and comparative examples are summarized in Table 1 below:

[0139] Table 1

[0140]

[0141] Preparation of solid-state batteries

[0142] The positive electrode, solid electrolyte membrane and negative electrode are stacked and assembled to obtain a solid-state battery. The positive electrode is NCM811 and the negative electrode is graphite.

[0143] Test Case

[0144] The film thickness, ion conductivity, porosity and volume change rate of the solid electrolyte membranes prepared in the above examples and comparative examples were measured. The results are shown in Table 2 below.

[0145] The utilization rate of the raw materials in the preparation process of the above examples and comparative examples was measured. The results are shown in Table 2 below.

[0146] The cycle performance of the battery comprising the solid electrolyte membrane prepared in the above examples and comparative examples was measured. The results are shown in Table 2 below.

[0147] Table 2

[0148]

[0149]

[0150]

[0151] From the data in the above table, it can be seen that by regulating the roughness and particle size of the solid electrolyte particles, the utilization rate of the raw materials can be effectively improved, that is, more solid electrolyte particles can enter the porous matrix, the contact and stacking between the solid electrolyte particles are improved, and become more compact. Under high pressure, the compression degree of the entire electrolyte membrane is small, and the volume change rate when switching between different pressure environments is small, so that in the battery, the solid electrolyte membrane and the electrode always maintain good contact, ensuring the good cycle performance of the battery. The above is only a speculation on the possible mechanism of this application and does not constitute a limitation on the scope of protection of this application.

[0152] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0153] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A method for preparing a solid electrolyte membrane, characterized in that: The following steps are involved: S1, ball-milling the solid electrolyte particles to obtain a first material; After ball milling, the roughness Ra of the solid electrolyte particles satisfies 1<Ra≤1.2, and the particle size D50 of the solid electrolyte particles is 1μm~10μm; S2, laying a second material including at least the first material on one side surface of the porous substrate, performing a preliminary filling treatment, and obtaining a solid electrolyte membrane intermediate; S3. Pressing the solid electrolyte membrane intermediate to obtain a solid electrolyte membrane.

2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S1, the temperature of the ball milling treatment is -50°C to 25°C; And / or, the rotation speed of the ball milling treatment is 400r / min to 700r / min; And / or, the ball milling treatment time is 5h to 15h; And / or, the ball-to-material ratio of the ball milling treatment is 15:1 to 25:

1.

3. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S1, the ball milling process is performed by using two or three grinding balls with different particle sizes.

4. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The flow energy of the first material is 200 mJ to 600 mJ.

5. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The preliminary filling treatment step includes using a vibrating screen to vibrate the porous matrix after laying the second material; or, The second material on the porous substrate is rolled using a flexible roller to achieve preliminary filling and redistribution of the second material.

6. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: Before step S2, the method further includes the following steps: mixing the first material with a fiberizable binder and performing a fiberization treatment to obtain the second material.

7. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S3, the pressure of the pressing process is 2-3t; And / or, the pressing treatment time is 30s to 5min; And / or, the temperature of the pressing treatment is 80°C to 130°C.

8. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In the step S3, the pressing process is performed once.

9. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane is prepared by the preparation method according to any one of claims 1 to 8.

10. A solid-state battery, characterized in that: The solid-state battery comprises a solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8.